The role of Malaysian university-of-the-future in the digital era: international community engagement for improving the wellbeing of B40 young women in India through humanising digital entrepreneurship programme - Manan, Abdul; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
The advanced education framework in India is one of the biggest on the planet with 51,649 foundations. The enrolments have likewise observed a huge four-crease increment. Notwithstanding the expanded access, challenges remain. Lacking financing, illiteracy, overall guidelines, low employability of graduates and low quality of educators plague the area. This paper offers validated conceptual Malaysian UotF business model with focus on international community engagement programmes. The value proposition of the conceptual business model is to enhance the wellbeing of B40 young women in India through humanising digital entrepreneurship education activities and harnessing on the digital capability. The design and system thinking approach has been adapted in this paper to address the wellbeing issues of the Indian B40 young women through understanding their need, and then followed by building conceptual business models using modelling tools, i.e. Business model canvas (BMC) and Value proposition design canvas (VPC). The approach includes conducting literature review and interviews for understanding the needs, challenges and key problems; formulating and ideating initial business model options in solving the problems; and validation of the initial business model by interviewing the various customer segments. The objective is to enhance the wellbeing of B40 young women with decent jobs and stimulate economic growth by humanising digital entrepreneurship programme.